Integrasi Nilai-nilai TRINGA dalam Bimbingan Kelompok Teknik Sosiodrama untuk Mencegah Perilaku Microagressions Siswa SMP - Alief Laili Budiyono; Henny Indreswari; Nur Eva (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Microaggressions are insults to individuals or groups carried out verbally or non-verbally, intentionally or unintentionally, which can have a psychological impact on the individual or group being targeted. Microaggressions have an impact on individual mental health so efforts are needed to prevent student microaggression behavior. So this research aims to: (1) describe the factors that cause student microaggression behavior; (2) constructing TRINGA values ​​in sociodrama techniques to prevent student microaggressions. A literature review is the research method used in this research. The research results show that there are six factors that cause student microaggression behavior, including gender, age, religious stereotypes, perceived inferiority, and non-religious assumptions. TRINGA values ​​can be used by counselors in providing sociodrama technique group guidance services. It is hoped that future researchers can test the effectiveness of TRINGA values ​​in group guidance on sociodrama techniques to prevent junior high school students' microaggressions behavior.